2019
DOI: 10.1590/1807-1929/agriambi.v23n9p702-708
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and thermodynamic properties of ‘bacaba’ pulp drying

Abstract: This study aimed to dry ‘bacaba’ (Oenocarpus bacaba Mart.) pulp under different thermal conditions, fit different mathematical models to the dehydration curves, and calculate the diffusion coefficients, activation energy and thermodynamic properties of the process. ‘Bacaba’ fruits were meshed to obtain the pulp, which was dried at temperatures of 40, 50 and 60 °C and with thickness of 1.0 cm. Increase in drying temperature reduced the dehydration times, as well as the equilibrium moisture contents, and drying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
(50 reference statements)
0
9
0
13
Order By: Relevance
“…The enthalpy (Δ H ) varied from 24.96 to 24.63 J mol −1 , and higher values with respect to this parameter were obtained at lower temperatures which shows the water evaporation process, taken place in the product, and occurs more slowly under these conditions. According to Morais et al, 44 Δ H represents the energy needed to promote the removal of water from the sample during the drying process. The authors observed a similar behaviour when drying bacaba pulp, which presented values of Δ H that varied from 34.23 to 34.40 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The enthalpy (Δ H ) varied from 24.96 to 24.63 J mol −1 , and higher values with respect to this parameter were obtained at lower temperatures which shows the water evaporation process, taken place in the product, and occurs more slowly under these conditions. According to Morais et al, 44 Δ H represents the energy needed to promote the removal of water from the sample during the drying process. The authors observed a similar behaviour when drying bacaba pulp, which presented values of Δ H that varied from 34.23 to 34.40 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…For the CB powder, the convective drying process was carried out in a greenhouse with air circulation (Tronh brand, model 170) at 60 °C (Morais et al, 2019). The pulp was placed on a tray, in order to allow perpendicular air flow and simulate the thin-layer drying process.…”
Section: Raw Materials and Sample Preparationmentioning
confidence: 99%
“…method stands out for the feasibility and simplicity of the process, which thus affects the cost and benefit (Morais et al, 2019). The freeze-drying process is another promising method in drying food (Costa et al, 2019), as its operation is based on the sublimation process with high pressures and low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, to attain 0.1 moisture ratio (MR = 0.1), the sample dried at 65°C prerequisite the minimum period (2.5 hr) trailed by 60°C sample (3.1 hr) and samples dried at 55°C took the highest time (3.7 hr). Hence greater temperature could provide a quicker drying rate (Morais et al., 2019). Excessive temperature and lower humidity, drying rate might rise firstly; in contrast as drying headways case hardening occurs (Okos et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For example, to attain 0.1 moisture ratio (MR = 0.1), the sample dried at 65°C prerequisite the minimum period (2.5 hr) trailed by 60°C sample (3.1 hr) and samples dried at 55°C took the highest time (3.7 hr). Hence greater temperature could provide a quicker drying rate (Morais et al, 2019).…”
Section: Impact Of Temperature On Drying Behaviormentioning
confidence: 99%